2018
DOI: 10.1016/j.adro.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiation therapy for adrenal gland metastases: Outcomes and toxicity

Abstract: PurposeThis study aimed to report on our institutional experience in the use of stereotactic body radiation therapy (SBRT) for the treatment of adrenal gland metastases. Specifically, we examined the outcomes and toxicity from this treatment modality on adjacent organs at risk.Methods and MaterialsData were retrieved from patients with adrenal metastases who were treated with SBRT between 2008 and 2017. Patients with primary adrenal malignancies were excluded. Toxicities were graded in accordance with the Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 67 publications
5
32
0
Order By: Relevance
“…While SBRT is well established and widely applied in the treatment of pulmonary and hepatic oligometastases [17][18][19][20], the literature for adrenal metastases is scarce. Predominantly small and retrospective studies exist which do not primarily focus on oligometastatic or oligoprogressive disease, but also include patients treated with palliative intent [21][22][23][24][25][26][27]. Furthermore, these studies only report limited details on radiotherapy planning and requirement for forced dose restrictions due to the close proximity to radiosensitive organs-at risks (OARs).…”
Section: Introductionmentioning
confidence: 99%
“…While SBRT is well established and widely applied in the treatment of pulmonary and hepatic oligometastases [17][18][19][20], the literature for adrenal metastases is scarce. Predominantly small and retrospective studies exist which do not primarily focus on oligometastatic or oligoprogressive disease, but also include patients treated with palliative intent [21][22][23][24][25][26][27]. Furthermore, these studies only report limited details on radiotherapy planning and requirement for forced dose restrictions due to the close proximity to radiosensitive organs-at risks (OARs).…”
Section: Introductionmentioning
confidence: 99%
“…Adrenal radiation is a well-established noninvasive treatment option for malignant metastases to the adrenal glands. Dosing is determined on the basis of tumor size and location, and ranges between 20 to 70 Gy in 1 to 15 fractions (12)(13)(14). The most common side effects are low grade gastrointestinal-related symptoms (nausea, diarrhea, abdominal pain) and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…The most common side effects are low grade gastrointestinal-related symptoms (nausea, diarrhea, abdominal pain) and fatigue. Low grade adrenal insufficiency has also been reported and is primarily seen in patients receiving radiation to bilateral adrenal glands (12,13). In their analysis of toxicities, Toesca et al (13) showed that SBRT had no short-term impact on renal function with a mean estimated decline in glomerular filtration rate of only 2.6 ± 8 mL/min/1.73 m 2 compared with baseline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stereotactic body radiotherapy (SBRT) has been suggested as an alternative, non-invasive ablative treatment by several authors [3,6,7]. One and three year local rates are reported of more than 80% [8]. Furthermore, SBRT resulted in low rates of toxicity, mostly grade 2 acute toxicity was found [6,7].…”
Section: Introductionmentioning
confidence: 99%